Livestock future in North Africa. How can scientific knowledge progress, technical innovation implementation and local empiric norms and practices be improved? - Chiche J. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
Two main findings can explain the gaps observed between the knowledge and practices of livestock actors in North Africa: (1) the breeders need time to experiment scientists proposals before either they adopt them, with or without changes and adaptation, or they forsake them; and (2) in live sciences and practices, since imponderable and unpredictable facts compel to look at scientific rules and reference models in perspective, it’s difficult to implement, and, even more, to integrate into a system, accurate standardized procedures (especially in the dry and semi-arid areas). Taking in account these two aspects in consulting and training design and management of livestock systems requires: (1) that field managers are constantly careful to avoid ignoring (even, and often, unintentionally) the empiric knowledge based on a continuous survey of the whole system they are involved in, since (i) it is the main tool to achieve breeder’s participation in an innovation trend, and (ii) even more, to avoid inciting (again, unintentionally) these breeders to drop out their own traditional and local practices; and (2) that fundamental researchers, by monitoring of the changes in their original findings throughout the experiments done by the users, improve and refine their knowledge of the progress, limits and enhancement achieved by every step that follows the formal transfer of a technology.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)